EFECTS ON LEVELS OF DEFOLIATION AND GROWTH STAGE ON YIELD AND SEED YIELD COMPONENTS OF SOYBEAN - Fontoura, Tatiana Brum; Costa, José Antonio; Daros, Edelclaiton (Scientia Agraria, 2006)
The objective of this research was to evaluate the effect of levels and growth stage of defoliation intensity and timing on grain yield and yield components of no-till soybean. The experiment was performed at the Estação Experimental Agronômica da UFRGS, in the growing season 2002/2003. The experimental desin was a randomized complete block, with sub-subplots, and four replications. The treatments were defoliation at three development stages (V9 – nine node; R 2 – flowering; R5 – begining of seed fill; R6 – maximum seed volume), two defoliation levels (33 and 100%) two row spacing and a check, without leaf removal. The short season CEP/CD 41 cultivar was used. Row spacing reduction from 40 to 20 cm increase grain yield even with defoliation. Yield reduction in R2 and R5, was greater with total defoliation. The most critical stage for leaf area removal was R5, the yield reduction increasing with the intensification of defoliation. The yield component with most reduction with defoliation was pods per m2, particularly with 100% defoliation at the begining of seed filling.